A new potential biomarker for 1-testosterone misuse in human urine by liquid chromatography quadruple time-of-flight mass spectrometry1. Issue 11 (7th June 2015) - Liu, Yang; Lu, Jianghai; Yang, Sheng; Xu, Youxuan; Wang, Xiaobing
<x xml:space="preserve">Abstract</x> In this study, 1-testosterone urinary metabolic profiles were investigated by liquid chromatography quadruple time-of-flight mass spectrometry (LC-QTOF-MS) using full scan and targeted MS/MS techniques with accurate mass measurement.